Pelatihan Pengolahan Data Statistik Dengan Eviews Pada Mahasiswa Manajemen Universitas Bumigora - Saputra, Sahdan; Hadi, Heri Sopian (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
The EViews program training aims to enhance the quality of scientific work by management students at Bumigora University through mastering statistical data analysis. This community service activity is structured, including preparation, implementation, and evaluation stages. The preparation phase involves identifying participants' needs, developing the curriculum, and preparing training materials. During implementation, participants receive a basic understanding of statistical theory, demonstrations on using EViews, and hands-on practice with relevant case studies. Evaluation is conducted to assess participants' knowledge and skills through tests, project assessments, and feedback collection. The evaluation results indicate that the training successfully improved participants' ability to use EViews for data analysis, positively impacting the quality of their scientific work. Feedback from participants also suggests that the training is relevant to their academic needs and highly beneficial in overcoming challenges in statistical data processing. In conclusion, this EViews training effectively enhances students' competence in statistical data analysis and is expected to be implemented continuously to support students' academic and research activities in the future.